Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory